Neuroactive Steroids and Cognitive Functions in First-Episode Psychosis Patients and Their Healthy Siblings - Knytl, Pavel; Voráčková, Veronika; Dorazilová, Aneta; Rodriguez, Mabel; Cvrčková, Aneta; Kofroňová, Edita; Kuchař, Martin; Kratochvílová, Zuzana; Šustová, Petra; Čerešňáková, Silvie; Mohr, Pavel (Frontiers in Psychiatry, 2019)
Background: Neuroactive steroids (NAS) affect neurotransmitter systems and cognition; thus, they play role in etiopathogenesis of psychiatric disorders. Aims: To examine cognition and effects of NAS on cognitive functioning in first-episode psychosis patients and in their healthy siblings. Secondary aims were to verify whether cognitive deficit is an endophenotype of psychosis and higher NAS levels represent a high-risk factor for psychosis. . Methods: Studied were: (1) patients with first episode of psychosis; (2) healthy siblings of the patients; (3) matching healthy controls. Study procedures included administration of a battery of neuropsychological tests assessing six cognitive domains, and examination of NAS plasma levels (cortisol [CORT], 11-deoxycorticosterone [DOC], testosterone [TEST], dehydroepiandrostendione [DHEA], dihydrotestosterone [DHT], progesterone [PROG]). Results: The total of 67 subjects was analyzed (16 patients, 22 siblings, 29 controls). Significant group differences were found in most of the cognitive domains; the patients had the lowest scores. Kruskal-Wallis test revealed significant group differences in CORT levels (p<0.01), TEST (p<0.01), DHT (p<0.001); no difference was found in PROG, DHEA, and DOC. All cognitive domains, except for attention, were affected by the NAS levels. CORT levels of patients correlated with speed of processing (r=0.55), working memory (r=0.52); PROG levels with abstraction (r= -0.63). In siblings, there was a negative correlation between TEST levels and verbal memory (r= -0.51) and PROG with attention (r= -0.47). Conclusions: Our results verified that individual domains of cognitive deficit (abstraction, verbal memory) can be considered as endophenotype of psychosis. Higher levels of cortisol and testosterone in siblings are consistent with high-risk states for psychosis. Multiple interactions between NAS and cognitive functioning, particularly memory functions, were observed. Study limitations (small sample size, administration of antipsychotic medication) did not allow to establish unequivocally NAS as an endophenotype.